If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2-3r-3=1
We move all terms to the left:
2-3r-3-(1)=0
We add all the numbers together, and all the variables
-3r-2=0
We move all terms containing r to the left, all other terms to the right
-3r=2
r=2/-3
r=-2/3
| 1.3=1.2y | | 9-2p=81 | | 1/2(h+4)=48 | | 5(2-x)-5(x+6)/1-3x=10 | | 5^n=12^2 | | 4x2-6x=14 | | 3(2x+2)=3x−15. | | 0.75x2.5=0.25x7.5 | | 0.75x2.5=0.25x | | 6x+3=4x5 | | 13(m-4)-3(m-9)-6(m+4)=0 | | 2x-20=4x-50 | | 8/11=64/x | | 20+15x=35+13x | | 9/3=45/x | | 7/x=30/15 | | 14y-(6y+4)=3y+5(y-1) | | 4x-2=-11x | | x/3=10+2 | | m-6/2=4 | | 5x/2-x/3=-9 | | 4x+8x=17-9-1 | | 2(x+8)=6x-16 | | 6x-1|-10=-5 | | 3x^2+2x=9x+20 | | 8-h=-3 | | 8^x=1/0 | | 1/3x=10+2 | | y^2=-14y | | -30=18+x | | 26.4=6.6d | | (1/2)b+(4/5)=b-(3/10) |